The prevalence of smartphone addiction and its related risk factors among Palestinian high school students: a cross-sectional study - Ahmead, Muna; Maqboul, Etaf; Alshawish, Eman; Dweib, Mohammad (Frontiers in Psychiatry, 2025)
BackgroundSmartphone addiction is a significant social and health problem. There is limited research on smartphone addiction in Palestine. The current study aimed to assess the prevalence of smartphone addiction and its association with sociodemographic variables, depression, anxiety, and social support among 12th grade students.MethodsThe study utilized a cross-sectional research design. A self-reported questionnaire, including the Smartphone Addiction Scale (SPAS), the OSLO Social Support Scale, and the Hospital Anxiety and Depression Scale (HADS), was used to gather data.ResultsA total of 1,083 participants were recruited, of whom 27.3% had depression, 50.5% had anxiety, 57.3% experienced smartphone addiction, and 17.6% had strong social support. The study found that students with weak or moderate teacher relationships (AOR: 2.854, p < 0.001), disrupted sleep with smartphones (AOR: 2.143, p < 0.001), negative impact of smartphone usage on studies (AOR: 3.016, p < 0.001), and poor or weak social support (AOR: 3.051, p < 0.001) were at risk of smartphone addiction. Participants who reported no impact on their sleep time (AOR: 0.478, p-value = 0.001), used smartphones for less than 2 hours daily (AOR: 0.347, p < 0.001), and used smartphones for 2 to 3 hours daily (AOR: 0.684, p = 0.037) were less likely to develop smartphone addiction.ConclusionSmartphone addiction was prevalent in high school students in this study. Weak teacher relationships, sleep disturbances, negative academic effects, and insufficient social support may lead to smartphone addiction. Programs that educate students, parents, and educators on smartphone addiction can prevent it and help detect and manage smartphone use problems.